Release velocity ImprovemenT with a new Metronome guIding chest COmpressions: The RITMICO simulation study - Maria Luce Caputo; Giuliana Monachino; Ruggero Cresta; Alessia Currao; Enrico Baldi; Simone Savastano; Andrea Cortegiani; Mariachiara Ippolito; Sara Accetta; Alessandra Gargano; Camilla Metelmann; Bibiana Metelmann; et al. (Resuscitation Plus)
Background and trial design: Outcomes of out-of-hospital cardiac arrest vary significantly, often due to the quality of cardiopulmonary resuscitation (CPR) provided. Automated real-time feedback devices have been explored to enhance CPR skills, but few devices currently ensure proper chest recoil. This study aimed to assess whether a double-click metronome could improve chest compressions (CC) metrics and particularly CC release velocity (CCRV) during CPR manikin simulation. Methods: We developed and tested a double-click metronome for CPR, where the first click signals the compression and the second click marks the end of chest release. We performed a multicenter non-blinded, randomized, controlled trial including volunteers with different levels of CPR expertise. Three CC metrics—depth, rate, and CCRV—were measured using an automated external defibrillator equipped with pads for CPR quality analysis. Results: 503 volunteers participated in the study, with 54% being male and a mean age of 34 ± 12 years. The median CCRV and CC depth achieved with the double-click metronome were significantly higher compared to the standard metronome (median difference 6 mm/s, IQR-15.2, 28.5, +1.5%, p < 0.001; median difference 0.1 cm, +2.5%, IQR −0.1, 0.4, p < 0.001). The double-click metronome led to significant improvements in CC depth and CCRV across all volunteer categories, with the greater effect observed in first responders and in non-specialized healthcare personnel. Conclusions: Compared to a standard metronome, the double-click metronome significantly enhances CPR quality. If further validated in real resuscitations, this new audio prompt could be a valuable tool for integration into devices designed for out-of-hospital cardiac arrest resuscitation, as well as a training tool to improve CPR quality.